2020
DOI: 10.37358/rc.20.2.7919
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Basic Blue-41 dye from Water by Stabilized Magnetic Iron Nanoparticles on Clinoptilolite Zeolite

Abstract: In this work, Zeolite/Fe3O4 nanocomposite used for adsorption of Blue 41 cationic dye from aqueous solutions in a wide range of concentrations. Analyzes of FTIR, XRD, FESEM, VSM and XRF have confirmed the nature and the structure of Zeolite/Fe3O4 nanocomposite adsorbent. The obtained results and analyzes determined that adsorption process efficiency increases by increasing reaction time, pH and amount of adsorbent and versus, increasing dye initial concentration causes significant decrease of adsorption effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Afshin et al 27 used Zeolite/Fe 3 O 4 nanocomposite to adsorb the basic blue-41 cationic dye. The obtained results showed that the efficiency of the adsorption process increases with increasing the reaction time, pH, and the adsorbent amount.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afshin et al 27 used Zeolite/Fe 3 O 4 nanocomposite to adsorb the basic blue-41 cationic dye. The obtained results showed that the efficiency of the adsorption process increases with increasing the reaction time, pH, and the adsorbent amount.…”
Section: Introductionmentioning
confidence: 99%
“…The removal efficiency of 71.4% was achieved under optimum conditions of pH = 9, the reaction time of 60 min, the adsorbent amount of 3 g L −1 , and the initial concentration of 100 mg L −1 . The results revealed that Zeolite/Fe 3 O 4 nanocomposite could be used as an available, environmentally friendly, and cost-effective adsorbent for the removal of dyes from effluents of various industries 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Optimum conditions for the adsorption of BGD on R-TNP, R-CLP, CA-TNP, and CA-CLP were determined by studying the various factors and parameters such as temperature, pH, adsorption dose, contact time, and agitation speed [69].…”
Section: Optimization Of Parametersmentioning
confidence: 99%
“…For the pseudo-second-order mechanism, the linear form is given in equation ( 13) [69,90] and is graphically expressed in Figure 16.…”
Section: Equilibrium Isothermal Studiesmentioning
confidence: 99%
“…Due to the presence of numerous hazardous chemicals, discharge of dyes into aquatic bodies without proper purification causes significant health hazards [7][8][9]. e existence of sulfur, heavy metals, nitrates, and naphthol leads to skin irritation, liver damage, or dysfunction of the kidney.…”
Section: Introductionmentioning
confidence: 99%